MDCT Anatomy $1 (BBodys - Romano, Luigia; Fulciniti, Sonia; Silva, Massimo; Pinto, Antonio; SpringerLink (Online service) (Milano : Springer Milan, 2011)
Although already in its third decade, computed tomography (CT) remains a highly dynamic field. The rapid development of multidetector CT (MDCT) technology has challenged the radiological world, even more so with the increasing use of MDCT angiography and cardiac CT. State-of-the-art MDCT techniques have been further enhanced by innovative post-processing imaging software. The book MDCT Body Anatomy is designed to assist medical residents, imaging technicians, and clinicians. Its nearly 500 axial and multiplanar illustrations comprise a comprehensive MDCT anatomic atlas of the body able to provide prompt answers to imaging anatomy questions. The MDCT anatomy of the chest, abdomen, and pelvis is presented in three different parts, with every image containing an informative legend describing the anatomic section performed.
Keywords: Medicine; Radiology, Medical; Medicine & Public Health; Imaging / Radiology